The impact of the relationship with the Quran on academic achievement of IIUM IRKHS undergraduate students - Ibrahim , Esam Eltigani Mohamed; Alias, Alizi; Jani, Mohd. Shah; Fatah Yasin, Raudlotul Firdaus; Zakariyah, Luqman (2014)
The growth of any country depends largely on the quality of education it can provide. Malaysia in the 1970th had all the problems of a low-income, illiterate, and under-developed country. Since then it has witnessed phenomenal growth and development spurred primarily by educational transformations. One of the educational institutions that contributed to this development is the International Islamic University Malaysia (IIUM). It flooded the Malaysian job market with successful graduates and provided several other countries with well-rounded individuals for several decades. The success of IIUM graduates is a phenomenon worthy of being the subject of numerous studies. For start, this study focuses on the factors that have potentially influenced the academic achievement of IIUM IRKHS undergraduate students, particularly their relationship with one of the Holy monotheistic scriptures, the Qur’an. The reason for selecting the academic achievement is because several studies at the international level linked the academically successful students to be more stable in their employment, less dependent on public assistance, less likely to engage in criminal activity, more active as citizens and charitable volunteers, have higher self-esteem, have lower levels of depression and anxiety, are less likely to exhibit socially deviant behavior, and are less likely to engage in substance abuse. Although several studies focused on the factors that influence academic achievement of students, none of the studies has assessed the relationship with a Holy book as a possible factor. The significance of this study lies in the fact that it is, perhaps, the first study that analyzes and evaluates the Qur’an as a possible factor that influences the academic success of undergraduate university students. A questionnaire format is selected to gather primary information. The population for this study is made up of 90 local and international undergraduate students from the Kulliyyah (Faculty) of IRKHS in the IIUM Gombak campus. The selected variables are measured by using 5-point Likert Scale of 1 to 5, where 1 is being strongly disagreed and 5 being strongly agreed. The collected data is analyzed by using the Statistical Package for Social Science Program (SPSS). The types of analysis performed include: Descriptive (mean, standard deviation, Kurtosis, frequency table and variance), reliability (Cranach alpha), factor, validity, correlation, and multiple linear regression analysis. One of the preliminary findings of this study is that having a relationship with the Qur’an has positively influenced the academic achievement of students.